Cellular and humoral immunogenicity of recombinant Mycobacterium smegmatis expressing Ag85B epitopes in mice. Issue 1 (March 2016) - Kadir, Nur-Ayuni; Sarmiento, Maria E.; Acosta, Armando; Norazmi, Mohd-Nor
Abstract: Objective/background: The search for new vaccines more efficacious than bacille Calmette–Guérin for tuberculosis prevention is of paramount importance for the control of the disease. The expression of Mycobacterium tuberculosis antigens in Mycobacterium smegmatis is one of the current strategies for the development of new-generation vaccines against tuberculosis. The objective of this study was to evaluate the immunogenicity in mice of M. smegmatis expressing epitopes from Ag85B antigen. Methods: M. smegmatis expressing three T cell epitopes from M. tuberculosis Ag85B (P21, P26, and P53) was constructed (rMs064). rMs064 was used to immunize BALB/C mice for immunogenicity evaluation. The present study investigates the capacity of rMs064 to induce specific cellular and humoral immune responses against the expressed epitopes. Cytokine production upon stimulation with Ag85B peptides and specific total immunoglobulin G and immunoglobulin G subclasses were determined. Results: The results showed a significant production of interleukin-12 and interleukin-23 when splenocytes were stimulated with P21, P26, and P53 peptides, and interferon-γ after stimulation with P21 in animals immunized with rMs064 compared with controls. The total immunoglobulin G and its subclasses showed significant increases against the Ag85B epitopes in the sera of rMs064-immunized mice compared with the control groups. Conclusion: The results of this study support the future evaluation of rMs064 as a vaccine candidate against tuberculosis in challenge experiments.